Impacto do trabalho infantil sobre o rendimento escolar: uma avaliação do caso no Rio Grande do Sul - (:unkn) unknown (Universidade Federal do Pampa, 2016)
Studies that seek to elucidate and analyze the impact that child labor may have on school performance are gaining prominence, especially in Brazil. The United Nations (UN) through the International Labor Organization (ILO) and the Program for the Eradication of Child Labor (PETI), draw attention to the theme, with the aim of enabling society to improve its quality of life, Growth and economic-social development. One of the solutions proposed by these bodies is to stimulate investment in human capital, considering the school performance as an integral part of this capital. Based on this, this study evaluated the impact of child labor, both domestic and in the market, on school performance in Rio Grande do Sul. Data from the Brazil Proof (2013) and the Propensity Score Matching methodology were used. Kassouf (2007) addresses the issue of child labor in an attempt to identify what drives families to expose children to work. In this way, we distinguish paid work, such as the one where the child needs to work to help with family expenses, and work at home, in which the child performs domestic duties at home, without receiving any remuneration whatsoever. However, when performing household activities, it also helps the family income, for example, it performs the activities that a maid or a nanny would do, in addition to allowing parents to spend more hours in the labor market. The work at home can be seen as positive by providing the child / adolescent with a sense of responsibility. The importance of evaluating the impact of child labor on school performance in the state of Rio Grande do Sul is due to the fact that it shows the peculiar aspects of this region and how the result can indicate policies to reduce child labor, A better use of education and the accumulation of human capital. The results show that work at home has a positive effect on the school performance evaluated by the Portuguese test and negative on the Mathematics test, which contradicts the hypothesis that it could, in its entirety, help in the process of creating a sense of responsibility. As expected, children and adolescents who work both in the market and in both are more affected than those who work only at home, as it has a decrease in school performance, reaching a loss of points around 12.73 in the Proof of Portuguese and 7,12 in mathematics evaluating the 9th grade students who work in the market. In mathematics, considering students working in both types, inside and outside the home, the losses are 12.92 and 8.27 in Portuguese and mathematics, respectively. The impact for young people in 9th grade is higher than when compared to 5th grade students for the different types of work considered here. These results are important in directing public educational policies, such as the adoption of full-time education, thus preventing these young people from working in the labor market
Keywords: Child labor; School performance; Economy: Brazil: Rio Grande do Sul; Economia: Brasil: Rio Grande do Sul; Trabalho infantil; Rendimento escolar